(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The Vietnam Trade Union organization was established on July 28, 1929, associated with the national liberation struggle movement led by President Ho Chi Minh and the Communist Party of Vietnam. Over nearly a century (90 years) of operation, Vietnam Trade Union has become an increasingly important position in the socialist-oriented market economy in Vietnam, especially the role of protecting workers’ rights. dynamic in the process of Vietnam’s international integration.